Fabry disease: a case report - Alam, Afroja; Sharleen, Nadia; Prianka, Nusrat Jahan; Rahman, Muhammad Raquib; Yesmin, Mahbuba; Asaduzzaman, ATM; Azad, Md Abul Kalam (BIRDEM Medical Journal, 2021)
Fabry disease is a rare X-linked recessive inborn error of metabolism due to deficient activity of the lysosomal enzyme, a-galactosidase A (a-Gal A). This results in the tissue accumulation of uncleaved glycosphingolipids within vascular endothelial lysosomes of various organs including skin, heart, kidneys and brain. We report a case of Fabry disease, in an 18-year-old boy, who presented with unilateral leg swelling and angiokeratoma corporis diffusum. Birdem Med J 2021; 11(2): 145-147